2022
DOI: 10.3390/ph15070806
|View full text |Cite
|
Sign up to set email alerts
|

In the Search for Novel, Isoflavone-Rich Functional Foods—Comparative Studies of Four Clover Species Sprouts and Their Chemopreventive Potential for Breast and Prostate Cancer

Abstract: Despite a significant amount of research, the relationship between a diet rich in isoflavones and breast and prostate cancer risk is still ambiguous. The purpose of the current study was to pre-select the potential candidate for functional foods among red, white, crimson, and Persian clover sprouts, cultured for different periods of time (up to 10 days), with respect to the isoflavone content (determined by HPLC-UV-VIS), and to verify their impact on hormone-dependent cancers in vitro. The red clover sprouts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…This observation can be explained by the concentration of isoflavones and phenolic acids, as these sprouts contained the highest amount of the compounds, e.g., the 5LM sprouts had the highest amount of isoflavones, while the 5DM, 6D, and 7DM sprouts were the richest in phenolic acids. The comparison of our results with those obtained by Galanty et al (2022) for white clover sprouts showed higher antioxidant activity for control sprouts as well as for the sprouts grown under stress conditions (simulated microgravity and total darkness) [18]. Based on these results, it can be concluded that stress conditions like simulated microgravity and the lack of sunlight during the early stage of sprouting can stimulate the antioxidant activity of the sprouts.…”
Section: Antioxidant Activitysupporting
confidence: 85%
See 2 more Smart Citations
“…This observation can be explained by the concentration of isoflavones and phenolic acids, as these sprouts contained the highest amount of the compounds, e.g., the 5LM sprouts had the highest amount of isoflavones, while the 5DM, 6D, and 7DM sprouts were the richest in phenolic acids. The comparison of our results with those obtained by Galanty et al (2022) for white clover sprouts showed higher antioxidant activity for control sprouts as well as for the sprouts grown under stress conditions (simulated microgravity and total darkness) [18]. Based on these results, it can be concluded that stress conditions like simulated microgravity and the lack of sunlight during the early stage of sprouting can stimulate the antioxidant activity of the sprouts.…”
Section: Antioxidant Activitysupporting
confidence: 85%
“…Similarly to that study, it was found that white clover contained isoflavones such as ononin and formononetin, but additionally we also found daidzin. Ononin and formononetin concentrations were significantly higher in our previous study [18]. This discrepancy in the results may be caused by the use of different clover varieties; in this study, we used Trifolium nano repens seeds, and in the previous study, Trifolium repens Grasslands variety was used.…”
Section: Amount Of Bioactive Compoundsmentioning
confidence: 55%
See 1 more Smart Citation
“…For the determination of polyphenols in plant extract samples the HPLC method, previously described [55] was used. The HPLC system consisted of a Dionex 100 (Dionex Softron GmbH, Germering, Germany) with a Photodiode 100 detector.…”
Section: Hplc Analysismentioning
confidence: 99%
“…This bioprocess also enhances vitamin and bioactive compound levels. Common seeds used for sprouts include alfalfa (Logan et al, 2001 ; Zhang et al, 2022 ), broccoli (Chiriac et al, 2020 ; Subedi et al, 2019 ), clover (Dębski et al, 2021 ; Zhang et al, 2022 ), radishes (Subedi et al, 2019 ), rapeseed (Galanty et al, 2022 ), Chinese cabbage, red cabbage, barley, and wheat (Xiao et al, 2022 ). However, the contents may differ depending on the cultivation method of the plant (Galanty et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%